Dual cross-linked collagen DLP 3D printing bio-ink, preparation method and application
Through the dual cross -linking collagen biological ink, combined with DLP 3D printing and optical cross -linking technology, the collagen biological ink has the problem of insufficient mechanical strength and anti -degradation capabilities in DLP 3D printing, and realizes high mechanical performance and anti -degradation water. Gel preparation has significantly promoted the repair effect in biomedical applications.
Patent Information
- Application Number
- CN202410720303.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2025-01-28
AI Technical Summary
The existing collagen bioinks have low mechanical strength and weak anti-degradation ability in DLP 3D printing, which limits their use in biomedical applications, and the residue of chemical crosslinking agents may cause toxicity, affecting clinical applications.
The biological ink with dual cross -linking collagen, including methyl acrylic collagen, optical cause, ultraviolet absorbent, and DPPA solution, and prepare hydrogels with high mechanical performance and anti -degradation capabilities through DLP 3D printing and optical connection technology Essence
Realize the high mechanical performance, preservation and anti -degradation ability of collagen biological ink, significantly promote the orderly deposition of collagen, promote the regeneration and repair speed of the epidermis, and have good biocompatibility and biological activity. Preparation of skin and bone cartilage repair materials.
Smart Images

Figure CN119367606A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of collagen DLP 3D bioprinting, and specifically relates to a double-crosslinked DLP 3D printing collagen bio-ink, a preparation method and an application thereof. Background Art
[0002] 3D printing technology, also known as additive manufacturing technology, has developed rapidly in recent years. Digital Light Processing (DLP) 3D printing technology converts three-dimensional solid model slices into two-dimensional data files and uses a digital micromirror system to photocuring liquid resin layer by layer until the entire model is formed. This technology is particularly suitable for printing small models that require fine details due to its fast and high-precision characteristics, and has wide application potential in the field of disease-directed treatment.
[0003] In theory, DLP 3D printing technology can print any designable model; however, in practice, due to the limitations of bio-ink performance, DLP 3D printing is difficult to achieve high precision, and some printing materials cannot be effectively formed. Therefore, DLP 3D printing places stringent requirements on the bio-ink used. It not only needs to have excellent printability and high mechanical strength, but also needs to have suitable anti-degradation properties and good biocompatibility if used in the medical field. It can be seen that bio-ink is a key element in DLP 3D printing.
[0004] Collagen, as an important functional protein in the human body and one of the widely used biomaterials, can bind to many cell surface receptors to regulate cell adhesion, proliferation and migration. It is widely used in the field of tissue engineering due to its good biocompatibility and low immunogenicity. However, researchers have found that when collagen is directly used as bio-ink for DLP 3D printing, the hydrogel printed has low mechanical strength and weak anti-degradation ability, which seriously limits its application in biomedicine.
[0005] In order to enhance the stability and mechanical properties of bio-ink, technicians in this field often use chemical cross-linking agents to cross-link, which is widely used to improve the mechanical properties of proteins. However, the residue of chemical cross-linking agents may produce potential toxicity, which seriously restricts its clinical application. Therefore, developing a method with good cross-linking effect, no toxic side effects, and significantly enhancing the strength of hydrogels has become a technical problem that technicians in this field urgently need to solve. Summary of the invention
[0006] In view of the above technical problems, the present invention provides a double cross-linked collagen bio-ink, which has good fluidity and photocuring performance. Through DLP 3D printing, a hydrogel with good mechanical properties, fidelity and anti-degradation ability can be prepared; the hydrogel has good biocompatibility and biological activity, and can significantly promote the orderly deposition of collagen, promote epidermal regeneration, and accelerate the repair speed. The double cross-linked collagen bio-ink is widely used in the field of tissue engineering for preparing skin repair materials and bone cartilage repair materials.
[0007] Specifically include the following:
[0008] The primary purpose of the present invention is to provide a double cross-linked collagen bio-ink, which comprises the following components: 0.5% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.05% to 0.5% m / v UV absorber and 0.001% to 0.01% m / v DPPA solution.
[0009] Preferably, the collagen is yak collagen.
[0010] Preferably, the yak collagen is yak type I collagen, and / or yak type II collagen, and / or yak type II collagen.
[0011] Preferably, the photoinitiator includes one or more of LAP, TPO, and I2959.
[0012] Preferably, the photoinitiator is LAP.
[0013] Preferably, the ultraviolet absorber includes lemon yellow and / or food coloring brilliant blue.
[0014] Preferably, the ultraviolet absorber is lemon yellow.
[0015] The second object of the present invention is to provide a method for preparing the bio-ink, comprising the following steps:
[0016] (1) dissolving freeze-dried collagen sponge in acetic acid solution to prepare collagen solution, and slowly stirring to dissolve;
[0017] (2) adding sodium hydroxide solution to adjust the pH of the collagen solution obtained in step (1) to 7-9, and then adding methacrylic anhydride dropwise to maintain the pH of the solution at 7-8; reacting in an ice bath for 24 hours, dialyzing in ultrapure water, and freeze-drying to obtain a methacrylated collagen solution;
[0018] (3) A 0.5% to 1% m / v methacrylated collagen solution was prepared with a 0.5 M acetic acid solution, a 6 M sodium hydroxide solution was added to adjust the pH of the solution to neutral, 0.1% to 0.5% m / v photoinitiator, 0.05% to 0.5% m / v UV absorber and 0.001% to 0.01% m / v DPPA solution were added, the mixture was mixed well, and the bubbles were removed by centrifugation to obtain CMA-DPPA bio-ink.
[0019] Preferably, the amount of methacrylic anhydride added in step (2) is ten times the equivalent of collagen lysine.
[0020] The third object of the present invention is to provide a method for preparing a 3D printing functional living material, comprising: adding biological ink to a 3D bioprinter for 3D printing, and then performing photocrosslinking to obtain a 3D printing functional living material, wherein the biological ink is the biological ink or the biological ink prepared by the preparation method.
[0021] The fourth object of the present invention is to provide a 3D printing functional living material, which is obtained by sequentially subjecting the biological ink or the biological ink prepared by the preparation method to 3D printing and cross-linking treatment.
[0022] The fifth object of the present invention is to provide the application of the 3D printed functional living material in the preparation of skin repair materials, bone cartilage repair materials, and tissue engineering.
[0023] The beneficial effects of the present invention are as follows: (1) The present invention provides a dual cross-linked collagen bio-ink, the bio-ink comprising the following components: 0.5% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.05% to 0.5% m / v UV absorber and 0.001% to 0.01% m / v DPPA solution; (2) The bio-ink of the present invention has good fluidity and photocuring performance, and can be used to prepare hydrogels with good mechanical properties, fidelity and anti-degradation ability through DLP 3D printing; (3) The bio-ink DLP 3D printed hydrogel of the present invention can promote cell proliferation and has good biocompatibility and biological activity; (4) The 3D printed hydrogel of the present invention can significantly promote the orderly deposition of collagen, promote epidermal regeneration, and accelerate the repair speed; the dual cross-linked collagen bio-ink is widely used in the field of tissue engineering for preparing skin repair materials and bone and cartilage repair materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Methacryloyl Collagen-Crosslinker Solution
[0025] Note: (A) CMA-GA; (B) CMA-THPC; (C) CMA-DPPA.
[0026] Figure 2 Characterization of CMA-DPPA bio-ink Notes: (A) STL model; (B) DLP printing image of CMA bio-ink; (C) DLP printing image of CMA-DPPA-2 bio-ink; (D) In-situ curing storage modulus and loss modulus of CMA, CMA-DPPA-1 and CMA-DPPA-2 bio-inks; (E) Storage modulus and loss modulus of CMA, CMA-DPPA-1 and CMA-DPPA-2 hydrogels; (F) Stress-strain curves of CMA, CMA-DPPA-1 and CMA-DPPA-2; (G) Young's modulus of CMA, CMA-DPPA-1 and CMA-DPPA-2 hydrogels; (H) Fourier transform infrared spectroscopy (FT-IR) of CMA and CMA-DPPA-2; (I) Crosslinking degree test of CMA, CMA-DPPA-1 and CMA-DPPA-2.
[0027] Figure 3 CMA-DPPA-2 bioink DLP bioprinting Notes: (A) Effects of slice thickness and exposure time on the printability of CMA-DPPA-2 bioink; (B) CMA-DPPA-2 bioink printing of succulent model; (C) CMA-DPPA-2 bioink printing of hollow model; (D) CMA-DPPA-2 bioink printing of hollow mesh model.
[0028] Figure 4 Characterization of collagen hydrogel properties Note: (A) DSC graph of CMA and CMA-DPPA-2 hydrogels; (B) Anti-degradation properties of CMA and CMA-DPPA-2 hydrogels; (C) Swelling properties of CMA and CMA-DPPA-2 hydrogels; (D) Average pore size of CMA and CMA-DPPA-2 hydrogels; (E) SEM image of CMA hydrogel; (F) SEM image of CMA-DPPA-2 hydrogel. Figure 5 CMA, CMA-DPPA-1 and CMA-DPPA-2 bio-inks have good biocompatibility and bioactivity. Note: (A) Live and dead cell staining; (B) Cytotoxicity; (C) Cell 3D imaging. (Scale bar: 200μm)
[0029] Figure 6 CMA, CMA-DPPA-1 and CMA-DPPA-2 bio-inks have good biological activity.
[0030] Note: (A) CLSM image of L929 on scaffold material, phalloidin staining F-actin (red) and Hoechst 33342 staining cell nuclei (blue); (B) cell migration.
[0031] Figure 7 CMA-DPPA-2 bio-ink loaded with cells for printing.
[0032] Note: (A) CMA-DPPA-2 bioink loaded with L929 cells prints a heart shape; (B) CMA-DPPA-2 bioink loaded with L929 cells prints a plum blossom pattern; (C) CMA-DPPA-2 bioink loaded with L929 cells prints a block diagram; (D) CMA-DPPA-2 bioink loaded with L929 cells prints a grid pattern.
[0033] Figure 8 CMA-DPPA-2 hydrogel promotes wound repair.
[0034] Note: (A) Photograph of wound healing; (B) Schematic diagram of changes in skin wound over time; (C) Closure rate of skin wound. Fig. 9 CMA-DPPA-2 hydrogel promotes wound repair tissue staining.
[0035] Note: (A) H&E; (B) Masson staining; (C) epidermal regeneration; (D) granulation tissue; (E) collagen deposition. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings of the specification. Obviously, the described embodiments are only a part of the present invention, not the whole of the invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that, in the following examples, unless otherwise specified, the methods used are all conventional methods; the reagents used are all conventional reagents and can be purchased from the market.
[0038] In the following examples, the collagen used was extracted in this laboratory. The extraction method is described in invention patent CN113520900B. However, the collagen described in the present invention is not limited to the above-mentioned collagen.
[0039] Example 1 Methacrylylated collagen-crosslinking agent solution
[0040] Prepare a 0.3% m / v collagen solution in a 0.5M acetic acid solution. After it is completely dissolved, add sodium hydroxide solution to adjust the pH to 7-9. Add ten times the equivalent of methacrylic anhydride (MA) of collagen lysine and keep the solution pH at 7-8. After reacting in an ice bath for 24 hours, dialyze in ultrapure water for 4 days and freeze-dry to prepare methacrylylated collagen (CMA).
[0041] The prepared CMA was dissolved in 0.5M acetic acid solution to prepare a 0.5% m / v solution, and the pH was adjusted to neutral. Then, 0.01% GA, THPC, and DPPA solutions were added respectively. The GA group formed a yellow gel, the THPC group gelled quickly and unevenly, and the DPPA group solution viscosity increased but still maintained fluidity. Therefore, in subsequent experiments, we chose DPPA as the crosslinking agent ( Figure 1 ).
[0042] Example 2 Preparation of bio-ink CMA-DPPA
[0043] The bio-ink mainly includes CMA solution, photoinitiator LAP, UV absorber UA and DPPA solution. CMA-DPPA bio-ink is prepared according to Table 1.
[0044] Table 1 Content of each component in different bio-inks
[0045]
[0046]
[0047] In bio-inks 1, 2, 3, and 4, CMA formed a uniform solution but could not gel; in bio-inks 5, 6, 7, and 8, CMA formed a uniform solution with high printing precision, and bio-ink 7 required a long printing time; bio-ink 8 had a fast printing speed and low precision, and high concentrations of LAP may be cytotoxic; in bio-inks 9, 10, 11, and 12, CMA had low solubility, high viscosity, and low printing precision. Therefore, we selected bio-inks 5 and 6 as printing inks for subsequent experiments.
[0048] In the following examples, bio-ink 6 is abbreviated as CMA-DPPA-1, and bio-ink 5 is abbreviated as CMA-DPPA-2.
[0049] In the following examples, unless otherwise specified, the bio-ink used in the experiments was CMA-DPPA-2, and CMA-DPPA-2 hydrogel was obtained by printing.
[0050] Example 3 Synthesis and characterization of methacrylylated collagen-dimethylphenylphosphonate (CMA-DPPA) bio-ink
[0051] CMA-DPPA-1 and CMA-DPPA-2 prepared in Example 2 were used to carry out this experiment.
[0052] The printing performance of CMA-DPPA-2 bio-ink was tested by DLP 3D printing of complex CAD models ( Figure 2 A). CMA biohydrogel has poor formability and collapses ( Figure 2B); while CMA-DPPA-2 hydrogel showed the same shape characteristics as the originally designed CAD model ( Figure 2 C). The results show that DPPA can enhance the photocuring performance of CMA and achieve high-precision printing.
[0053] Strain-dependent oscillatory rheology showed that the applied strain within the linear viscoelastic region (LVR) did not change the G' value of the hydrogel, showing characteristics similar to those of a viscoelastic solid ( Figure 2 D). In LVR, the G' values of CMA, CMA-DPPA-1 and CMA-DPPA-2 are 521.44, 945.06 and 658.09 Pa respectively. The uniaxial compression test results show that ( Figure 2 E), the compressive strengths of CMA, CMA-DPPA-1 and CMA-DPPA-2 were 17.15 kPa, 35.12 kPa and 37.88 kPa, respectively. The results showed that DPPA improved the mechanical properties of CMA-DPPA hydrogel by cross-linking with CMA.
[0054] The compressive strength of the hydrogel was evaluated by uniaxial compression test. The stress-strain curve showed that the ultimate fracture strength (UFS) of CMA was 17.15 kPa at a strain of 36.10%. The UFS of CMA-DPPA-1 and CMA-DPPA-2 were 35.12 kPa and 37.88 kPa at strains of 34.34% and 33.52%, respectively. Figure 2 F). The Young's moduli of CMA, CMA-DPPA-1 and CMA-DPPA-2 are 6.14 kPa, 13.90 kPa and 15.13 kPa respectively ( Figure 2 G). These results further indicate that DPPA improves the mechanical properties of CMA-DPPA-1 and CMA-DPPA-2 hydrogels by cross-linking with CMA.
[0055] The mechanism of action of DPPA and CMA was investigated by Fourier transform infrared spectroscopy (FT-IR). The C=O bond vibration peak in the FT-IR spectrum of CMA is located at 1644 cm -1 , while in CMA-DPPA-2 it shifts to 1660 cm -1 , indicating that the carbonyl groups on the surface of collagen molecules participate in cross-linking. In the FT-IR spectrum, the amide II peak in CMA is located at 1564 cm -1 , while in CMA-DPPA-2 it shifts to 1578 cm -1 The results show that in CMA-DPPA-2 hydrogel, the -NH 2 Cross-linking with -COOH ( Figure 2 H).
[0056] In addition, we used the TNBS method to detect the cross-linking degree of CMA-DPPA-1 hydrogel and CMA-DPPA-2 hydrogel ( Figure 2 I). The cross-linking degree of CMA is 96.15%, while the cross-linking degrees of CMA-DPPA-1 hydrogel and CMA-DPPA-2 hydrogel are 98.12% and 98.54%, respectively. 2 The cross-linking improves the printing performance of CMA.
[0057] Example 4 CMA-DPPA-2 bio-ink DLP bio-printing
[0058] We investigated the effects of layer thickness and exposure time on the printing conditions of CMA-DPPA-2 bio-ink by measuring the DLP 3D printing conditions of CMA-DPPA hydrogels with a diameter of 7 mm and a height of 2 mm under different conditions ( Figure 3 A). The results show that when the exposure time is the same, the diameter of the hydrogel gradually decreases with the increase of the slice thickness; when the slice thickness is the same, the diameter of the gel gradually increases with the increase of the exposure time. Under the conditions of slice thickness of 100μm, exposure time of 15s, slice thickness of 50μm, exposure time of 15s, the diameter of the cylindrical gel of CMA-DPPA is closer to the set value of 7mm. Therefore, we choose to print when the slice thickness is 100μm and the exposure time is 15s.
[0059] In addition, we designed CAD models of complex 3D structures such as fleshy and hollow structures for DLP printing and verified the printing performance of CMA-DPPA-2 bio-ink ( Figure 3 BD). All printed hydrogels showed the same shape characteristics as the originally designed CAD models, indicating that the CMA-DPPA-2 bioink has good printability. These results show that DPPA can enhance the photocuring properties of CMA and achieve high-precision DLP 3D printing.
[0060] Example 5 Characterization of CMA and CMA-DPPA-2 hydrogel properties
[0061] The thermal stability of CMA-DPPA-2 hydrogels was investigated by differential scanning calorimetry (DSC). Figure 4 A). The results show that the thermal transition temperature of CMA is about 84.4℃, while the thermal transition temperature of CMA-DPPA-2 is 100.6℃, which is much higher than that of CMA. The results show that DPPA improves the thermal stability of CMA by cross-linking with CMA.
[0062] The degradation resistance of CMA and CMA-DPPA-2 hydrogels was evaluated by in vitro enzymatic degradation ( Figure 4 B). In a solution containing 5 U / mL of collagenase, the degradation rate of CMA was as high as 41.5% on the first day, while the degradation rate of CMA-DPPA-2 hydrogel was only 32.2%. On the 11th day, the degradation rate of CMA was 69.9%, and the degradation rate of CMA-DPPA-2 hydrogel was 52.0%. The results show that CMA-DPPA-2 hydrogel exhibits excellent resistance to collagenase-mediated degradation.
[0063] The stability of CMA and CMA-DPPA-2 hydrogels in solution was evaluated by swelling ratio (SR) test. CMA hydrogel reached equilibrium within 5 h, and its SR was about 61. However, CMA-DPPA-2 hydrogel reached equilibrium at about 3 h, and its SR was about 58. The results showed that CMA-DPPA-2 hydrogel had a lower swelling ratio and showed higher stability ( Figure 4 C).
[0064] The microstructure of CMA and CMA-DPPA-2 hydrogels was examined by scanning electron microscopy (SEM). Figure 4 E, F). SEM results showed that the freeze-dried hydrogels of CMA and CMA-DPPA-2 hydrogels had porous network structures, with average pore sizes of 112.5±10.8μm and 75.7±14.6μm, respectively. Figure 4 D) The results further show that DPPA and CMA are cross-linked.
[0065] Example 6 Biocompatibility and bioactivity of CMA, CMA-DPPA-1 and CMA-DPPA-2 bioinks
[0066] To investigate the cytotoxicity of CMA, CMA-DPPA-1 bio-ink, and CMA-DPPA-2 bio-ink, we performed CCK-8 assay ( Figure 5 B). After 24 hours of co-culture with L929 cells, the cell viability of CMA, CMA-DPPA-1 hydrogel and CMA-DPPA-2 hydrogel was greater than 100%. This indicates that CMA, CMA-DPPA-1 hydrogel and CMA-DPPA-2 hydrogel have good biocompatibility.
[0067] L929 cells were encapsulated in CMA, CMA-DPPA-1, and CMA-DPPA-2 hydrogels, and their bioactivity was further evaluated by live / dead cell staining. Live / dead cell staining images of CMA, CMA-DPPA-1, and CMA-DPPA-2 hydrogels showed that there were a large number of live cells in all three hydrogels, among which the number of live cells in CMA-DPPA-2 hydrogel was the largest ( Figure 5 A). In addition, the live / dead cell staining 3D images of CMA-DPPA-2 hydrogels showed that L929 cells were evenly distributed in the hydrogels and grew well ( Figure 5 C) These results all indicate that CMA-DPPA-2 hydrogel has excellent biological activity.
[0068] We observed the adhesion and spreading characteristics of L929 cells on CMA and CMA-DPPA-2 hydrogel substrates using fluorescence confocal microscopy ( Figure 6 A). Fluorescence images show that cells on CMA and CMA-DPPA hydrogels are slender spindle-shaped, indicating that both CMA and CMA-DPPA hydrogels can promote cell adhesion. Among them, the number of cells in CMA-DPPA hydrogel is larger and the spreading area is larger. The results show that CMA-DPPA hydrogel has a strong ability to promote cell adhesion.
[0069] The effect of collagen bio-ink on cell migration was evaluated by cell scratch test results ( Figure 2-6 B). Microscope images show that after 24 hours of cell culture, fewer cells migrated in the blank group, while a large number of cells migrated to the scratch area in the CMA and CMA-DPPA hydrogel groups ( Figure 6 B). Among them, CMA-DPPA hydrogel has the highest migration rate. These results show that CMA-DPPA hydrogel can significantly promote cell migration.
[0070] In addition, we further investigated the bioactivity of CMA-DPPA-2 hydrogel by cell-loaded DLP 3D printing. CMA-DPPA-2 hydrogel was mixed with L929 cells as bio-ink for 3D bioprinting to further investigate the bioactivity of the hydrogel. Figure 7 As shown. The live and dead cell staining results of the DLP bioprinted heart, plum blossom, square, and grid showed that the cells grew well and were evenly distributed on the hydrogel. These results show that the CMA-DPPA-2 hydrogel-loaded cell bio-ink DLP 3D printing material has high cell survival rate and printing accuracy, and has broad application prospects in the field of tissue repair.
[0071] Example 7 CMA-DPPA-2 hydrogel promotes skin wound healing
[0072] We constructed a full-thickness skin defect model in SD rats to evaluate the ability of CMA-DPPA-2 hydrogel to promote full-thickness skin defect repair in vivo. CMA and CMA-DPPA-2 hydrogels with a diameter of 13 mm and a height of 3 mm were prepared and implanted into skin defects with a diameter of 13 mm, respectively. The effect of the hydrogel material on skin defect repair was evaluated 7, 14, and 21 days after implantation.
[0073] The wound healing of rats was assessed by taking photos ( Figure 8 ). After 7 days of treatment, the wound healing photos taken showed that the wound area of the blank group, CMA group and CMA-DPPA-2 hydrogel group was reduced. However, pustules appeared in the wound of the blank group. The wound healing rate of the CMA-DPPA-2 hydrogel group was about 52.29%, while the wound healing rates of the blank group and CMA group were only 21.7% and 38.32%. 14 days after surgery, the wound area of the CMA-DPPA-2 hydrogel group was the smallest, and the wound closure rate was 94.54%. The wound closure rates of the blank group and CMA group were 64.07% and 78.96%, respectively. After 21 days of treatment, the wound in the CMA-DPPA-2 hydrogel group was almost completely healed, consistent with the color of the adjacent skin tissue, and the wound closure rate was as high as 97.78%. There were still unhealed wounds in the blank group, and there were small wound remnants in the CMA group, and scar tissue appeared; the wound healing rates of the blank group and CMA group were 64.07% and 80.39%, respectively. The results showed that CMA-DPPA-2 hydrogel had the ability to significantly promote the repair of full-thickness skin damage in rats.
[0074] To evaluate the effect of collagen hydrogel on the repair of full-thickness skin defects, we performed histological analysis ( Fig. 9 H&E staining was used to evaluate the granulation tissue formation and epidermal regeneration in the full-thickness skin defect model of SD rats at different time points ( Fig. 9 A, C, D). After 7 days of treatment, the CMA-DPPA-2 hydrogel group and the CMA group had more granulation tissue than the blank group, indicating that the CMA-DPPA-2 hydrogel group promoted the regeneration of granulation tissue; 14 days after surgery, the regeneration of granulation tissue in both the CMA-DPPA-2 hydrogel group and the CMA group was significantly reduced, indicating that the damaged tissue had begun to repair. On the 21st day, there was still limited granulation tissue regeneration in the blank group, while there was almost no granulation tissue in the CMA-DPPA-2 hydrogel group and the CMA group, indicating that the damaged tissue had been basically repaired ( Fig. 9 D). During the treatment period, epidermal regeneration in the CMA-DPPA-2 hydrogel group and the CMA group was significantly higher than that in the blank group ( Fig. 9 C). These results indicate that the wound healing in the CMA-DPPA-2 hydrogel group was more complete, with significant re-epithelialization, granulation tissue formation, and new skin attachment formation.
[0075] Masson trichrome staining was used to evaluate collagen deposition in wound regeneration sites. Fig. 9 B, E). On the 7th day, new collagen fibers were formed in the skin defect sites of the blank group, CMA group and CMA-DPPA-2 group, accounting for 6.45%, 18.02% and 28.73% respectively. After 14 days of treatment, the number of collagen fibers in the CMA-DPPA-2 hydrogel group and the CMA group was 60.04% and 41.06%, respectively, while that in the blank group was only 15.57%. After 21 days of culture, the CMA-DPPA-2 hydrogel group and the CMA group regenerated a large number of dense collagen fibers, 76.08% and 62.3%, respectively, while the regenerated collagen fibers in the blank group were sparsely distributed, only 30.03%. Masson staining results showed that the collagen fibers in the blank group were disordered. In contrast, the collagen deposition in the CMA-DPPA-2 hydrogel group was the thickest, the density was the largest, and the arrangement was the most uniform. In summary, the consistent results of H&E and Masson staining showed that the CMA-DPPA-2 hydrogel group could effectively promote skin tissue repair.
[0076] In summary, the present invention provides a double cross-linked collagen bio-ink, the bio-ink comprising the following components: 0.5% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.05% to 0.5% m / v UV absorber and 0.001 to 0.01% m / v DPPA solution; the bio-ink of the present invention has good mechanical properties, thermal stability and anti-degradation properties, and can achieve high-precision DLP 3D printing; and the bio-ink described in the present invention adds a photoinitiator, an ultraviolet absorber and DPPA at the same time, which is simple and convenient, and the obtained bio-ink has more stable mechanical properties; while the existing bio-ink needs to be immersed in chemical cross-linking after printing, and the chemical cross-linking agent is located on the surface of the material, resulting in the disadvantages of complete external cross-linking, incomplete internal cross-linking and unstable material; the bio-ink described in the present invention can promote cell proliferation and has good biocompatibility and biological activity; the bio-ink described in the present invention can significantly promote the orderly deposition of collagen, promote epidermal regeneration, and accelerate the repair speed, and can be used in the preparation of skin repair materials, bone cartilage repair materials, and tissue engineering.
Claims
1. A double cross-linked collagen DLP 3D printing bio-ink, characterized in that: The biological ink comprises the following components: 0.5% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.05% to 0.5% m / v ultraviolet absorber and 0.001% to 0.01% m / v DPPA solution.
2. The bio-ink according to claim 1, characterized in that: The collagen is yak collagen.
3. The bio-ink according to claim 2, characterized in that: The yak collagen is type I yak collagen, and / or type II yak collagen, and / or type Ш yak collagen.
4. The bio-ink according to claim 1, characterized in that: The photoinitiator includes one or more of LAP, TPO and I2959.
5. The bio-ink according to claim 1, characterized in that: The ultraviolet absorber includes lemon yellow and / or food coloring brilliant blue.
6. The method for preparing the biological ink according to any one of claims 1 to 5, characterized in that: The steps include: (1) dissolving freeze-dried collagen sponge in acetic acid solution to prepare collagen solution, and slowly stirring to dissolve; (2) adding sodium hydroxide solution to adjust the pH of the collagen solution obtained in step (1) to 7-9, and then adding methacrylic anhydride dropwise to maintain the pH of the solution at 7-8; reacting in an ice bath for 24 hours, dialyzing in ultrapure water, and freeze-drying to obtain methacrylated collagen; (3) A 0.5% to 1% m / v methacrylated collagen solution was prepared with a 0.5 M acetic acid solution, a 6 M sodium hydroxide solution was added to adjust the pH of the solution to neutral, 0.1% to 0.5% m / v photoinitiator, 0.05% to 0.5% m / v UV absorber and 0.001% to 0.01% m / v DPPA solution were added, the mixture was mixed well, and the bubbles were removed by centrifugation to obtain a bio-ink.
7. The method for preparing the biological ink according to claim 6, characterized in that: The amount of methacrylic anhydride added in step (2) is ten times the equivalent of collagen lysine.
8. A 3D printing functional living material, characterized in that: The method is as follows: adding biological ink to a 3D bioprinter for printing, and then performing photocrosslinking to obtain a 3D printing functional living material, wherein the biological ink is the biological ink described in any one of claims 1 to 5 or the biological ink prepared by the preparation method described in any one of claims 6 to 7.
9. Application of the 3D printed functional living material as claimed in claim 8 in the preparation of skin repair materials, bone and cartilage repair materials, and tissue engineering.
Citation Information
Cited By
Composite bio-ink for constructing tissue engineering skin through 3D printing as well as preparation method and application of composite bio-ink
CN120478726A